Calceolaria dichotoma subsp. colimana (Calceolariaceae), a new subspecies from western Mexico - Padilla-Velarde, Eloy; Cuevas-Guzmán, Ramón (Instituto de Ecología, A.C., 2010)
Calceolaria dichotoma subsp. colimana is described and illustrated as a new subspecies from the state of Colima in western Mexico. C. dichotoma belongs to subgenus Cheiloncos and section Micranthera, previously only known from the Andes, from Colombia to the north of Argentina. The finding of the taxon in Colima increases thousands of kilometers to the north the known distribution of the subgenus, section and species.